1999
DOI: 10.1016/s0893-133x(99)00024-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naltrexone and Fluoxetine on Alcohol Self-Administration and Reinstatement of Alcohol Seeking Induced by Priming Injections of Alcohol and Exposure to Stress

Abstract: We have recently shown that priming injections of alcohol and footshock stress reinstate alcohol seeking in drug-free rats. Here we tested whether naltrexone and fluoxetine, two drugs used in the treatment of alcohol dependence, would affect reinstatement of alcohol seeking induced by these events. We also determined the effects of these drugs on alcohol self-administration during the maintenance phase. Rats were trained to press a lever for a 12% w/v alcohol solution. After stable drug-taking behavior was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(112 citation statements)
references
References 56 publications
11
97
2
2
Order By: Relevance
“…When footshocks were massed closely together within the selfadministration context, there was reinstatement, but this was not specific to the active lever, which is consistent with findings that shocks evoke general activity both during and soon after their presentation (Fanselow 1982). Although other studies have documented shock-induced reinstatement, the specificity of this effect to the drug-seeking lever is not always clear (see Shaham et al 1998;Lê et al 1999;Liu and Weiss 2002;McFarland et al 2004).…”
Section: Discussionsupporting
confidence: 73%
“…When footshocks were massed closely together within the selfadministration context, there was reinstatement, but this was not specific to the active lever, which is consistent with findings that shocks evoke general activity both during and soon after their presentation (Fanselow 1982). Although other studies have documented shock-induced reinstatement, the specificity of this effect to the drug-seeking lever is not always clear (see Shaham et al 1998;Lê et al 1999;Liu and Weiss 2002;McFarland et al 2004).…”
Section: Discussionsupporting
confidence: 73%
“…3). The ability of stress to increase alcohol seeking (Lê et al 1998(Lê et al , 1999(Lê et al , 2000Weiss 2002a, 2003;Martin-Fardon et al 2000) is consistent with stress enhancing the probability of relapse and furthering alcohol abuse. Further, the risk of relapse in alcoholics is reportedly increased by stress (Brown et al 1990(Brown et al , 1995Pohorecky 1991;Sinha 2001), with anxiety during abstinence being a predictor of endstate drinking (Kushner et al 1994(Kushner et al , 2000(Kushner et al , 2001Sloan et al 2003;Willinger et al 2002).…”
Section: Stress During Withdrawal From Multiple Alcohol Exposures Incmentioning
confidence: 75%
“…Utilization of the sucrose-fading procedure to obtain reliable bar pressing for ingestion of alcohol is a popular apvproach to investigate alcohol drinking (Brown et al 1998;Ciccocioppo et al 2004;Lê et al 1999Lê et al , 2003Rogowski et al 2003;Roberts et al 1996;Samson 1986;Valdez et al 2002;Weiss et al 1993). However, while extended absence from bar pressing increased intake when alcohol was restored in some investigations (i.e., similar to alcohol deprivation; Heyser et al 1997;Hölter et al 1997;McKinzie et al 1998), Samson and Chappell (2001) found no effect of deprivation on intake using a limited access operant procedure.…”
Section: Repeated Alcohol Withdrawals and The Alcohol-deprivation Effmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we do not know whether the small oral priming dose of ethanol alone could have reinstated responding, or whether the environmental cues associated with ethanol availability and the orosensory properties of ethanol acted additively to induce reinstatement. In this context, it is worth noting that although contingent or injected ethanol have been previously reported to reinstate ethanol responding, this effect shows high variability and inconsistency (Chiamulera et al, 1995;Lê et al, 1998Lê et al, , 1999Vosler et al, 2001;Lê and Shaham, 2002).…”
Section: Discussionmentioning
confidence: 98%